Biologically relevant laminin as chemically defined and fully human platform for human epidermal keratinocyte culture. Issue 1 (December 2018) - Tjin, Monica; Chua, Alvin; Moreno-Moral, Aida; Chong, Li; Tang, Po; Harmston, Nathan; Cai, Zuhua; Petretto, Enrico; Tan, Bien; Tryggvason, Karl
Abstract The current expansion of autologous human keratinocytes to resurface severe wound defects still relies on murine feeder layer and calf serum in the cell culture system. Through our characterization efforts of the human skin basement membrane and murine feeder layer 3T3-J2, we identified two biologically relevant recombinant laminins—LN-511 and LN-421- as potential candidates to replace the murine feeder. Herein, we report a completely xeno-free and defined culture system utilizing these laminins which enables robust expansion of adult human skin keratinocytes. We demonstrate that our laminin system is comparable to the 3T3-J2 co-culture system in terms of basal markers' profile, colony-forming efficiency and the ability to form normal stratified epidermal structure in both in vitro and in vivo models. These results show that the proposed system may not only provide safer keratinocyte use in the clinics, but also facilitate the broader use of other cultured human epithelial cells in regenerative medicine. In vitro expansion of human epidermal keratinocytes to resurface severe wound defects still relies on a human/mouse xenograft culture system. Here the authors develop a fully human, xeno-free culture system using skin-associated laminins, normally present in vivo, to replace mouse feeder cells.